Bifunctional sphingosine for cell-based analysis of protein-sphingolipid interactions - Haberkant, Per; Stein, Frank; Höglinger, Doris; Gerl, Mathias; Brügger, Britta; Van Veldhoven, Paul P.; Krijgsveld, Jeroen; Gavin, Anne-Claude; Schultz, Carsten (ACS chemical biology, 2016)
Sphingolipids are essential structural components of cellular membranes and are crucial regulators of cellular processes. While current high-throughput approaches allow for the systematic mapping of interactions of soluble proteins with their lipid-binding partners, photo-cross-linking is the only technique that enables for the proteome-wide mapping of integral membrane proteins with their direct lipid environment. Here, we report the synthesis of a photoactivatable and clickable analog of sphingosine (pacSph). When administered to sphingosine-1-phosphate lyase deficient cells, pacSph allows its metabolic fate and the subcellular flux of de novo synthesized sphingolipids to be followed in a time-resolved manner. The chemoproteomic profiling yielded over 180 novel sphingolipid-binding proteins, of which we validated a number, demonstrating the unique value of this technique as a discovery tool. This work provides an important resource for the understanding of the global cellular interplay between sphingolipids and their interacting proteins.